Meningkatkan Minat Belajar Siswa dengan Menggunakan Teknologi Multimedia (Wordwall) pada Pembelajaran Seni Budaya Kelas VII di Tingkat SMP - Sriwahyuni, Nefi; Safrizal; Kafryati, Bettri; Angelia, Nola; Asmiati; Aslita (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This classroom action research aims to increase students' interest in learning in class VII at junior high school level. The school used as the treatment site was SMPN 8 Tanjung Jabung Timur. This is based on a lack of interest in studying arts and culture because of online learning which was previously carried out in elementary schools and only assignments were given via WhatsApp messages. The use of multimedia technology used in this PTK is the use of wordwall. This research uses the classroom action research method, which is better known as classroom action research. In the research subject class, the number of participants was 16 students in class VII at junior high school level. The instrument for this research is a descriptive teacher assessment journal. After implementing it in cycle one for 4 meetings, it was found from the results of the teacher's assessment journal that students' interest in learning increased as indicated by indicators of interest in learning, namely feelings of happiness, student interest, student attention, student involvement. Therefore, this classroom action research has been said to have succeeded in achieving the target in the implementation of one cycle.